Current Pathogenetic Concepts of Vascular Cognitive Impairment - Kurt A Jellinger (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2016)
The term vascular cognitive impairment designates a heterogenous group of disorders ranging from mild cognitive impairment to full-blown dementia - vascular dementia - resulting from cerebrovascular lesions involving various brain areas. Current clinical criteria show moderate sensitivity (50-56%) and variable specificity (range 64-98%). The prevalence in autopsy series ranges from 0.03 to 58% (mean 8-15% in Western series, 22-35% in Japan). Major morphological types - multi-infarct and subcortical vascular encephalopathy, strategic infarct dementia, lacunar state, cortical granular atrophy (rare), and ischemic encephalopathy - are caused by atherosclerosis of major cerebral arteries and small vessel disease, resulting from systemic, cardiac and local vascular disease or cerebral amyloid angiopathy. Pathogenesis of vascular dementia is multifactorial, and pathophysiology affects brain areas and neurological networks involved in cognition, memory, behavior, and executive functions. Vascular brain injury in elderly persons often coexists with Alzheimer-type lesions and other pathologies resulting in mixed dementia. However, these lesions are also present in many non- demented elderly subjects. The heterogeneity of clinical manifestations, cerebrovascular pathology and their pathogenic factors result in limitations of the accuracy of diagnostic criteria for vascular dementia. Therefore, standardized and reproducible neuropathological criteria for the assessment of cerebrovascular lesions associated with cognitive impairment in order to elucidate contribution of cerebrovascular disease to cognitive impairment are urgently needed.